برنامج تدريبي وفق احتياجات المشرفين الإداريين في سلطنة عمان - Hamad Al-Shuaili, K.; Noorhayati Hashim (Universiti Sains Islam Malaysia, 2024)
This is a quantitative research disscusses the training needs by administrative supervisors. Open interviews with (20) administrative supervisors were conducted; confirmed the difficulties hinder the administrative supervisor work. The objective is to develop a training program for supervisors due to their needs. A questionnaire of (46) items was implemented to a sample of (70) supervisors. The statistical averages; standard deviations and relative importance of all paragraphs were extracted using the (SPSS) program. The findings revealed that (37) of the paragraphs in the questionnaire obtained an average of (3.00) or more, in the area of: (systems and regulations governing work, planning, administrative supervision strategies, professional development of school principals, preparation of training programs, Modern, community service) Which represents a training requirement for administrative supervisors and also showed differences between the responses of the study population due to the gender variable in the areas of planning and management supervision strategies for males. The researcher recommended the need to involve administrative supervisors in determining their training needs.